Language has a skin: philosophical elements for an Austinian reading of Spinoza - Bonfante, Gleiton (The ESPecialist, 2025)
This article describes theoretical-philosophical reading gestures that propose bringing affect, as understood by Spinoza in Ethics (2009[1677]), closer to Austin's Theory of Speech Acts (1990[1975]) for the composition of a theoretical-methodological perspective that privilege the body and affect in Applied Linguistics research. Two currents of thought on affect in contemporary times are presented, tensioning a point of contention: discourse. Next, Spinoza's theory of affectivity is presented to propose that affect is an effect of embodied meaning inherent to existence, which is discursive. Austin and Spinoza are then paired to project the perlocutionary dimension of the speech act as the affective dimension of language and thus suggest that incorporating the concept of affect into the pragmatics of the perlocutionary can provide a solid philosophical body for uilding analytical paths interested in the affective dispositions of discourse and semiosis in general. Austin's reading of Spinoza theoretically informed the thesis that language has a skin and that the interest in the body unites Spinoza's affective vulnerability with Austin's linguistic vulnerability.